2017
DOI: 10.1016/j.celrep.2017.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of P2Y6 Signaling in AgRP Neurons Reduces Food Intake and Improves Systemic Insulin Sensitivity in Obesity

Abstract: Uridine-diphosphate (UDP) and its receptor P2Y6 have recently been identified as regulators of AgRP neurons. UDP promotes feeding via activation of P2Y6 receptors on AgRP neurons, and hypothalamic UDP concentrations are increased in obesity. However, it remained unresolved whether inhibition of P2Y6 signaling pharmacologically, globally, or restricted to AgRP neurons can improve obesity-associated metabolic dysfunctions. Here, we demonstrate that central injection of UDP acutely promotes feeding in diet-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…These findings are consistent with the outcome of a recent study that reported improved insulin sensitivity in HFD mice lacking P2Y 6 R in whole body or specifically in AgRP neurons of the hypothalamus (20). The role of P2Y 6 R in controlling energy balance was also highlighted in a study demonstrating that increased plasma uridine levels in obesity increased hypothalamic UDP synthesis to activate AgRP P2Y 6 R, thereby increasing food intake (11).…”
Section: R Might Lead Tosupporting
confidence: 89%
“…These findings are consistent with the outcome of a recent study that reported improved insulin sensitivity in HFD mice lacking P2Y 6 R in whole body or specifically in AgRP neurons of the hypothalamus (20). The role of P2Y 6 R in controlling energy balance was also highlighted in a study demonstrating that increased plasma uridine levels in obesity increased hypothalamic UDP synthesis to activate AgRP P2Y 6 R, thereby increasing food intake (11).…”
Section: R Might Lead Tosupporting
confidence: 89%
“…At molecular level, several genes in AgRP neurons have been associated with this regulation of whole-body glucose homeostasis. For instance, the deletion of purinergic receptor 6 (P2Y6) specifically in AgRP neurons, improved systemic insulin sensitivity in obese mice [41] and similar results have been observed when the transcription factor activating transcription factor 4 (ATF4) was deleted specifically in AgRP neurons [42].…”
Section: Agrp Neurons and Glucose Metabolismsupporting
confidence: 55%
“…In the context of obesity, uridine levels are elevated in the circulation (Steculorum et al, 2015), indicating that the uridine/UDP system might be another mechanism that promotes the vicious cycle of increased weight gain along with exaggerated food intake. Consistent with this model, AgRP-neuron-specific P2Y6-deficient mice are protected from high-fat-diet-induced adiposity and insulin resistance (Steculorum et al, 2017) (see poster, Obese fasting state).…”
Section: New Perspectives In Cns-dependent Control Of Feeding Behaviomentioning
confidence: 80%